Manajemen Ekstrakurikuler pada Peserta Didik di Paud IT Alhamdulillah Yogyakarta - AULIA LAILY RIZQINA (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This study describes extracurricular management for students at Integreted Islamic Pre-School Alhamdulillah Yogyakarta. The purpose of this study was to find out how extracurricular management is implemented at Integreted Islamic Pre-School Alhamdulillah Yogyakarta. This paper was conducted using a qualitative method and a descriptive approach based on observations and interviews conducted at Integreted Islamic Pre-SchoolAlhamdulillah. Based on the research conducted, extracurricular activities at Integreted Islamic Pre-SchoolAlhamdulillah are carried out every day. The extracurricular activities that are carried out every day, namely: drum band, painting, and dancing. Extracurricular management is also carried out starting from the planning, organizing, implementing, and evaluating stages.